2006
DOI: 10.1016/j.ijsolstr.2005.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A solution to the thermo-elastic interface crack branching in dissimilar anisotropic bi-material media

Abstract: An interface crack or delamination may often branch out of the interface in a laminated composite due to thermal stresses developing around the delamination/crack tip when the media is exposed to heat flow induced by environmental events such as a sudden short-duration fire. In this paper, the thermo-elastic problem of interface crack branching in dissimilar anisotropic bi-media is studied by using the theory of StrohÕs dislocation formalism, extended to thermo-elasticity in matrix notation. Based on the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Hu Tuo [4] used finite element numerical simulation method to study the mechanism of the interface crack propagation in the composite materials, the result showed that the interface crack in the composite pressure vessel appeared elliptical propagation and propagated to the material with small elastic modulus. R. Li et al [5] researched the influence of the thermal load on the interface crack branched propagation in anisotropic elastic material using numerical simulation method. Yu Hanghai et al [6] studied the resistance force of crack propagation in BNNT/Si 3 N 4 composites with the finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…Hu Tuo [4] used finite element numerical simulation method to study the mechanism of the interface crack propagation in the composite materials, the result showed that the interface crack in the composite pressure vessel appeared elliptical propagation and propagated to the material with small elastic modulus. R. Li et al [5] researched the influence of the thermal load on the interface crack branched propagation in anisotropic elastic material using numerical simulation method. Yu Hanghai et al [6] studied the resistance force of crack propagation in BNNT/Si 3 N 4 composites with the finite element method.…”
Section: Introductionmentioning
confidence: 99%